Do(n't) worry, it's temporary: The effects of fixed-term employment on affective well-being - Paul Schumann; Lars Kuchinke (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper examines the impact of fixed-term employment on the affective and cognitive well-being of employees operationalized by the subjective frequency of the basic emotions of happiness, sadness, fear and anger as well as life satisfaction. Longitudinal effects were analysed across 10 waves of sampling from the Socio-Economic Panel (SOEP), an annual representative survey in Germany. Random effects within between model (REWB) analyses were applied to examine differences between fixed-term and permanent workers as well as within effects of a change of contract type. In addition, the impact of the direction of contract type change was evaluated by examining subsamples with changes from fixed-term to permanent and vice versa. The results suggest that fixed-term employees' affective well-being is lower, while cognitive well-being (or happiness) is hardly affected. A change from permanent to fixed-term contracts is associated with higher frequencies of self-reported fear and sadness experiences, while a change in the opposite direction results in lower frequencies. In addition, life satisfaction was only found to increase with the change from fixed-term to permanent employment. While the effect on fear is masked by job security, acting as a mediating factor, theeffect on sadness remains significant when the model is controlled for job security. Thus, by treating cognitive and affective well-being as separate constructs this study provides new insights into the psychological costs of fixed-term contracts and reveals the strong impact of fixed-term employment on self-reported experiences of sadness.
Keywords: 330; fixed-term employment; affective well-being; job security; job change; cognitive well-being; life satisfaction; hybrid models